2004
DOI: 10.1292/jvms.66.1229
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Variation of the Skull of the Lesser Mouse Deer

Abstract: ABSTRACT. We examined the geographical variation of the skull size and shape of the lesser mouse deer (Tragulus javanicus) from Laos, Thailand, Peninsular Malaysia, Sumatra, Java, Borneo, Langkawi and some Islands of Tenasserim in Myanmar. Although the influence of the climatic condition on skull size was not confirmed in the mainland populations, the skull became rostro-caudally longer in the populations of Tenasserim and Sumatra because of island isolation effect. The skull size was classified into the follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…More recently, Meijaard and Groves (2004) used a combination of external and craniometric features to justify recognition of two additional species from within the T. napu group -T. versicolor from south-east Vietnam and T. nigricans from Balabac Island. They also confirmed our earlier finding (Endo et al 2004b) of morphological differences in T. napu between populations from peninsular Malaysia and the islands of Indonesia. In the Lesser Mouse deer populations, Meijaard and Groves (2004) were unable to find substantial morphological differences between the populations in Laos, Vietnam and East Thailand (subspecies: affinis), and those on Borneo Island (subspecies: fulviventer and ravus).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…More recently, Meijaard and Groves (2004) used a combination of external and craniometric features to justify recognition of two additional species from within the T. napu group -T. versicolor from south-east Vietnam and T. nigricans from Balabac Island. They also confirmed our earlier finding (Endo et al 2004b) of morphological differences in T. napu between populations from peninsular Malaysia and the islands of Indonesia. In the Lesser Mouse deer populations, Meijaard and Groves (2004) were unable to find substantial morphological differences between the populations in Laos, Vietnam and East Thailand (subspecies: affinis), and those on Borneo Island (subspecies: fulviventer and ravus).…”
supporting
confidence: 92%
“…Although it is generally agreed that the two species differ in overall size, morphological studies of coat color, body proportions and skeletal morphology generally have failed to provide clear diagnoses of the two taxa (Miller 1900(Miller , 1902(Miller , 1903Thomas and Wroughton 1909;Kloss 1916Kloss , 1918Chasen 1935Chasen , 1940van Dort 1988van Dort , 1989Corbet and Hill 1992). In part, this reflects the presence of geo-graphic variation in size in both species, resulting in overlap between the two species in many external and skull measurements (Lekagul and McNeely 1988;van Dort 1988van Dort , 1989Corbet and Hill 1992;Endo et al 2004b). Van Dort (1989) concluded that the two species are distinguishable only on throat color and from multivariate analysis of the metatarsal bone and femur of adult specimens.…”
mentioning
confidence: 99%